Pollen preferences of stingless bees in the Amazon region and southern highlands of Ecuador by scanning electron microscopy and morphometry - Joseline Sofía Ocaña-Cabrera; Jonathan Liria; Karla Vizuete; Cristina Cholota-Iza; Fernando Espinoza-Zurita; Claude Saegerman; Sarah Martin-Solano; Alexis Debut; Jorge Ron-Román (PLoS ONE, 2022)
Stingless bees are effective pollinators of native tropical flora. Their environmental service maintains flow of pollen through pollination, increase reproductive success and influence genetic structure in plants. The management of stingless bees “meliponiculture”, is an activity limited to the countryside in Ecuador. The lack of knowledge of their managers about pollen resources can affect the correct maintenance/production of nests. The objective is to identify botanical families and genera of pollen grains collected by stingless bees by morphological features and differentiate potential species using geometric morphometry. Thirty-six pot pollen samples were collected from three Ecuadorian provinces located in two climatically different zones. Pollen type identification was based on the Number, Position, Character system. Using morphological features, the families and genera were established. Morphometry landmarks were used to show variation for species differentiation. Abundance, diversity, similarity and dominance indices were established by counting pollen grains, as well as spatial distribution relationships by means of Poisson regression. Forty-six pollen types were determined in two study areas, classified into 27 families and 18 genera. In addition, it was possible to identify more than one species, classified within the same family and genus, thanks to morphometric analysis. 1148 ± 799 (max 4211; min 29) pollen grains were counting in average. The diversity showed a high richness, low dominance and similarity between pollen resources. Families Melastomataceae and Asteraceae, genera Miconia and Bidens, were found as the main pollen resources. The stingless bee of this study are mostly generalist as shown the interaction network. The results of the present survey showed that stingless bees do not collect pollen from a single species, although there is evidence of a predilection for certain plant families. The diversity indexes showed high richness but low uniformity in the abundance of each family identified. The results of the study are also meaningful to the meliponiculture sector as there is a need to improve management practices to preserve the biodiversity and the environment.